Pemanfaatan Sosial Media Marketing sebagai Alat Pemasaran Efektif untuk Peningkatan Bisnis UMKM - Syukur, Agus; Widiastuti, Widiastuti; Surasati, Fajar; Mazia, Lia; Sasetio, Jalalludin; Hidayat, Irwan; Taqiyyah, Mia Risyah; Anggraini, Feni Savira; Rusmawati, Cikal Pustiprayata; Zhafira, Ryanne (Journal of Community Service and Society Empowerment, 2025)
This service to society is motivated by several important things, including; First, the increasingly rapid advances in technology and information require humans to be able to adapt to these developments, both by designing them, getting to know them, as well as operating and utilizing them. From a positive side, this can facilitate activities or transactions as well as human interaction in the virtual/digital world. Second, the majority of Indonesian people, especially in urban areas, still do not know or use technology for business activities. This is of course based on various things, including educational factors and experience factors. Furthermore, for rural communities as downstream communities, of course in time they will also experience adjustments to the development of this technology, so they are required to be able to understand and utilize it.   This community service aims to introduce technology for business activities and how to utilize various technological applications in digital business transactions and interactions. The result of this community service is that the perpetrators of the UMKM activities Songgo Jati Venue and Resto, Sentra Kota, Jl. Caman Raya No. 16 Block E3, Jatibening, Kec. Pondok Gede, Bekasi, West Java has understood the urgency and benefits of social media marketing as an effective marketing tool to increase MSME business activities. Some of the social media applications that have been practiced by MSMEs are websites, market places, social media (face book ads, tik tok ads, and instagram ads), and e-commerce, for example go food, shopee.